2007
DOI: 10.1074/jbc.m609521200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pseudophosphorylation and Cross-linking by Lipid Peroxidation and Advanced Glycation End Product Precursors on Tau Aggregation and Filament Formation

Abstract: Accumulation of hyperphosphorylated Tau protein as paired helical filaments in pyramidal neurons is a major hallmark of Alzheimer disease. Besides hyperphosphorylation, other modifications of the Tau protein, such as cross-linking, are likely to contribute to the characteristic features of paired helical filaments, including their insolubility and resistance against proteolytic degradation. In this study, we have investigated whether the four reactive carbonyl compounds acrolein, malondialdehyde, glyoxal, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 60 publications
0
69
0
1
Order By: Relevance
“…36 MGO, GO, and MDA are some of the most reactive compounds in terms of formation of tau dimers and higher molecular-weight oligomers. These modifications have been suggested as accelerating tangle formation in vivo, and as a consequence interference with the formation or the reaction of these reactive carbonyl compounds could be a promising way of inhibiting tangle formation and neuronal dysfunction in AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 MGO, GO, and MDA are some of the most reactive compounds in terms of formation of tau dimers and higher molecular-weight oligomers. These modifications have been suggested as accelerating tangle formation in vivo, and as a consequence interference with the formation or the reaction of these reactive carbonyl compounds could be a promising way of inhibiting tangle formation and neuronal dysfunction in AD.…”
Section: Discussionmentioning
confidence: 99%
“…These modifications have been suggested as accelerating tangle formation in vivo, and as a consequence interference with the formation or the reaction of these reactive carbonyl compounds could be a promising way of inhibiting tangle formation and neuronal dysfunction in AD. 36 The entorhinal cortex is the earliest cortical region affected by AD (stages I/II), followed by the hippocampus (stages III/IV). 20 In our study we observed a clear augmentation in the levels of nonenzymatic oxidative modifications in pro-NGF molecules in hippocampus and entorhinal cortex samples from AD-affected brains.…”
Section: Discussionmentioning
confidence: 99%
“…Acrolein has been reported to form a bis-adduct with lysine residues, named N ε -(3-formyl-3,4-dehydropiperidino)lysine (FDP-lysine) [33]. The electrophilic α,β-unsaturated carbonyl moiety is retained in FDP-lysine, allowing it to react further with sulfhydryl compounds, such as GSH [96], or other nucleophilic sites in proteins under formation of cross-links [97]. FDP-lysine has been detected immunochemically in brain tissue from Alzheimer's disease patients, particularly in neurofibrillary tangles of the microtubule-associated protein Tau [98].…”
Section: Acrolein Adduction To Amino Acids and Cross-linking Of Proteinsmentioning
confidence: 99%
“…Another approach to the inhibition of tangle formation might be the inhibition of tau crosslinking e.g. by advanced glycation endproducts by the use of anti-glycation agents (Kuhla et al 2007;Krautwald et al 2010;. Furthermore, it has been suggested that microtubule ( However, with growing uncertainty of the therapeutic potential of drugs targeting amyloid and tau, other novel therapies have recently been proposed, including those targeting glycation, oxidative stress and inflammation ).…”
Section: Anti-tangle Drugsmentioning
confidence: 99%